2020
DOI: 10.3390/atmos11010121
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Weather on the Behaviour of Tourists in a Beach Destination

Abstract: In sun-and-beach destinations, weather has a decisive influence on the variability of the daily flow of tourists. Uncertainty in demand flows directly affects businesses and employment. This work aims to improve understanding of the behaviour of tourists in response to changes in weather conditions. The analysis is carried out in the Rías Baixas, a sun-and-beach destination in north-west Spain. The paper analyses the relationship of weather conditions with daily flows during the high season at the main tourist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Another key difference is that when daily rain is greater than 25 mm, a penalty function is triggered (assigning a rating of −1) to signal the overriding effect rain has on tourism demand, as shown in revealed preference studies of beach tourists [41][42][43][44][45]. In terms of the HCI:Beach versus HCI:Urban, both are similar, with the exception of the ratings for moderate precipitation amounts (6-11 mm), with beach tourists more resilient to rain versus tourists on an urban holiday.…”
Section: Design Of the Hci:beachmentioning
confidence: 99%
“…Another key difference is that when daily rain is greater than 25 mm, a penalty function is triggered (assigning a rating of −1) to signal the overriding effect rain has on tourism demand, as shown in revealed preference studies of beach tourists [41][42][43][44][45]. In terms of the HCI:Beach versus HCI:Urban, both are similar, with the exception of the ratings for moderate precipitation amounts (6-11 mm), with beach tourists more resilient to rain versus tourists on an urban holiday.…”
Section: Design Of the Hci:beachmentioning
confidence: 99%
“…Jiang et al [ 18 ] used a social media survey and regression and variance analysis to find that particulate pollution negatively impacts the maximum number of park visits. R-Toubes et al [ 19 ] analysed the relationship between weather conditions and people flow, daily, at tourist beaches highlighting that sunshine is important. Zhao et al [ 20 ] found via a survey that in hazy weather, higher-income cyclists in Beijing tended to switch to use private vehicles rather than to use public transit, while lower-income cyclists were more likely to continue cycling.…”
Section: Related Workmentioning
confidence: 99%
“…Flexibility to adapt plans and opportunism to take advantage of weather conditions for bathing are key concepts for those visitors. The Atlantic seaboard of southwestern Europe can be included well into the category of "weather-sensitive" beach destinations because beach attendance is linked to clear skies and the lack of rainfall [6][7][8][9][10]. The region includes several resorts (e.g., La Toja, Santander and San Sebastian in Spain; Biarritz, Ille of Ré in France; and Brighton in the UK) whose long touristic traditions, linked to the "sea bathing" therapies among wealthiest, goes back to the middle of the 19th century.…”
Section: Introductionmentioning
confidence: 99%
“…The HCI: Beach integrates the thermal, physical, and aesthetic facets of the climatic variables relevant for this kind of tourism segment [28], its calculation is simple, and it has been tested empirically. It also recognizes the non-linear impact of certain variables on beach attendance, since both declared and stated preference studies emphasize clear skies and the lack of rain as the best weather conditions for beach attendance [8][9][10][29][30][31]. Therefore, the HCI: Beach also includes a penalizing function to account the overriding role of variables such as rain and wind speed.…”
Section: Introductionmentioning
confidence: 99%